Implementing WDEP Group Counseling to Reduce Intolerance and Foster Religious Moderation - Jeniva, Isabella; Asalaka, Merry Bendelina; Sendayu, Fendahapsari Singgih; Sikowai, Asnat Ningsi; Rumpaidus, Cornelia Inserayau; Aidit, Obet (JURNAL PENDIDIKAN, 2025)
Implementing WDEP Group Counseling to Reduce Intolerance and Foster Religious Moderation   Abstract Knowledge regarding religious attitudes that influence social life in schools is essential to be conveyed, not only through religious education subjects but also through activities that promote religious tolerance. This is conducted to realize religious moderation. Group counseling services using the WDEP technique are expected to be a solution to prevent intolerance and enhance students' ability to be tolerant amidst religious diversity. This study employed a research and development (R&D) approach using the Design-Based Research (DBR) methodology. The pretest results showed a high level of reduced intolerance in building religious moderation among students: 4 students (80%) in group 1, 1 student (20%) in group 2, and 2 students (40%) in group 3. Meanwhile, the posttest results indicated increased scores: 5 students (100%) in group 1, 3 students (60%) in group 2, and 3 students (60%) in group 3. The conclusion of this study is that the implementation of the WDEP technique group counseling prototype design has proven to be effective and feasible in reducing intolerance at SMAN 2. The implementation of the collaboratively designed WDEP technique counseling service resulted in the development of a WDEP Technique Group Counseling Service Guidebook.